Dissonant Voices: Memory and Counter-Memory in Manuel Vázquez Montalbán's Autobiografia del general Franco - José F. Colmeiro (Studies in 20th & 21st Century Literature, 1997)
Vázquez Montalbán's unauthorized autobiography of General Franco is built upon the use of dissonance as a strategy of resistance. The novel reveals the author's "professional schizophrenia" resulting from the dramatic authorial split as Franco's fictional ghostwriter and anti-Franco public persona, refracted internally in the split narrator of the text. This monumental construction of language and memories puts forth a metafictional examination of the conflicting relationship between history and fiction. Challenging traditional notions of authorship, referentiality, and self-referentiality, Autobiografia del general Franco obliges us to examine the dissonant discourses of historiography and memory and to ascertain the political function of writing as counter-discourse. Noise is an ubiquitous trope of dissonance throughout the novel, functioning as a privileged metaphor for the disrupting disturbances mobilized by resistance and counter-memory. Montalbán's novel opposes the repressed histories rewritten by multiple individual and collective memories against the official history written with a single monolithic voice, creating in the process an intertextual collective collage of different subjectivities, each struggling to insert its own story, its relative truth. This multiplicity of dissonant voices make up the "noise" that interferes with Franco's narrative and effectively creates a counter-memory. The dissonant voices of intertextuality are thus used in the novel as a powerful form of collective resistance.
Keywords: Manuel Vázquez Montalbán; General Franco; dissonance; resistance; ghostwriter; narration; memory; history; fiction; counter-memory; collective memory; individual memory; intertextuality; collective resistance